Estudos de solos do Triângulo Mineiro e de Viçosa: II- Adsorção de fosfatos - Prudente Santana , Derli; Moura Filho , Waldemar (Revista Ceres, 2025)
Phosphorus adsorption of fire soil samples from the Triângulo Mineiro and three from Viçosa, Minas Gerais, Brazil, was studied and its correlations with other characteristics investigated.